Authentic Happiness in Marriage: How Do Effective Communication and Positive Emotional Support Contribute? - Rizky, Muhammad; Nurfarhanah, Nurfarhanah; Karneli, Yeni; Ardi, Zadrian (Journal of Educational, Health and Community Psychology, 2024)
In today’s marriages, a common issue is the lack of effective communication and positive emotional support, which can lead to divorce and impact authentic marital happiness. This study aims to explore the relationship between effective communication, positive emotional support, and authentic happiness in marriage. A total of 72 couples participated in this research, selected through purposive sampling. Criteria included a marriage duration of no more than 5 years and an age range of 19-40 years for partners, aligning with early adulthood developmental theory. Data were analyzed descriptively, followed by prerequisite analysis and hypothesis testing using regression analysis. The results indicate a significant relationship between effective communication, positive emotional support, and authentic marital happiness. These findings have practical implications for premarital counseling and guidance programs, offering a reference for counselors to inform couples about the importance of effective communication and positive emotional support.